Microstructures of Development in the KDE-Electronic Mailing List - Ali, Aminul Islam (2007)
In light of the impressive innovation capabilities of Open Source Software (OSS) development communities, I propose that OSS-development communities innovate in temporally emergent, sequential and transient microstructures of development. To be specific, exploration and exploitation by means of continuous redesign occurs in brokerage and closure microstructures of development at the triadic-level. At the same time, the concepts of exploration and exploitation are redefined from the current contextualisation in learning and boundaries of learning to a context of knowledge sharing with which boundaries of space are replaced by boundaries of social-characteristics. I propose that exploration and exploitation are continuous in OSS-development for which there is the solution of punctuated-equilibrium to sustain a balance between the two through temporal sequences dependant on the context of the development activity. Furthermore, I propose that tasks of variation creation, selection and retention occurs in the microstructures of development and in which variation creation continues to manifest throughout the knowledge creation cycle. And all of which are validated using 139 discussion threads from the K-Desktop Environment (KDE) developer mailing list. The findings indicate that microstructures of development sustain cycles of exploration and exploitation, but in a temporal sequence through temporal cycling dependant on the context of the development activity, and lead to complete knowledge creation cycles in doing so.